Analisis Kelayakan Finansial Pengusahaan Kebun Hutan dengan Tanaman Buah Durian (Durio Zibethis Murr) di Kabupaten Kutai Kertanegara Propinsi Kalimantan Timur - H.A. Husainie Syahrani (Universitas Islam Indonesia, 2003)
The goal of the research understands the benefit level and eligibility durians (Durio Zibethinus Murr) forest garden business by financial analysis aspect in Kutai Kertanegara District East Kalimantan Province. Research methodologies we are using are field observation and interviews. Data processing by financial analysis such as payback period, NPV, Net Benefit Cost Ratio and Internal Rate of Return.The final results shows the development forest garden business by durians (Durio Zibethinus Murr) plantation is very benefit able and eligibility to develop on community development, it could be seen in NPV, Net Benefit Cost Ratio and Internal Rate of Return value: 20,94 % where every family need 0,5 ha land for discount rate 10%.